Analisis Pengawasan Impor Atas Barang Kiriman Dalam Rangka Meningkatkan Kepatuhan Pengguna Jasa Kepabeanan Pada Kantor Pelayanan Utama Bea dan Cukai Tipe C Soekarno Hatta - Hasanatul Chair Harahap; Ambarwati (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to analyze the monitoring mechanisms, obstacles encountered, compliance levels, influencing factors, and effectiveness of monitoring imports of shipped goods by the Soekarno-Hatta Type C Main Customs and Excise Office (KPUBC). The method used is qualitative descriptive with interviews conducted with eight informants, consisting of customs officials, academics, and importers. The results of the study show that supervision is carried out using a risk management approach, a selective system, and information technology. The main constraints are limited human resources and complex procedures. Compliance among service users has improved due to system transparency and regulatory education. Factors such as the professionalism of officials, clarity of rules, and past experiences also influence compliance. The effectiveness of supervision has been proven to encourage higher compliance. This study recommends strengthening the evaluation system, improving human resources, and simplifying procedures. Keywords Import Supervision, Consignments, Compliance, Customs and Excise, CEISA, PMK 96/2023